Soft Self-Healing Nanocomposites - Sanka, R. V. Siva Prasanna; Krishnakumar, Balaji; Leterrier, Yves; Pandey, Shyam; Rana, Sravendra; Michaud, Véronique (Frontiers in Materials, 2019)
This review article provides an overview of the research and applications of soft self-healing polymers and their nanocomposites. A number of concepts based on physical and chemical interactions have been explored to create dynamic and reversible gel and elastomer networks, each strategy presenting its own advantages and drawbacks. Physical interactions include supramolecular interactions, ionic bonding, hydrophobic interactions, and multiple intermolecular interactions. Such networks do not require external stimulus and are capable of multiple self-healing cycles. They are generally characterized by a rapid but limited healing efficiency. The addition of nanofillers enhances the mechanical strength of the soft networks as in conventional gels and elastomers, and do not compromise the network healing dynamics. In certain cases, nanofillers moreover trigger the healing process through e.g., multi-complexation processes between each component. Chemical interactions include Diels-Alder reactions and disulphide, imine, boronate ester, or acylhydrazones bonding, and are usually triggered with an external stimulus. The resulting healing is efficient, leading to good mechanical properties, but is generally slow at ambient temperatures, and dynamic chemical interactions are only reversible at higher temperatures. Conductive nanofillers were reported to speed up the healing process in such systems owing to their energy absorption properties. The challenges with nanofillers remain their functionalization and dispersion within the self-healing formulations. Soft self-healing gels and nanocomposites find applications in engineering such as coatings, sensors, actuators and soft robotics, and in the bio-medical field, including drug delivery, adhesives, tissue engineering and wound healing.